Knowledge, attitudes and practices about contraception amongst schoolgirls aged 12–14 years in two schools in King Sabata Dalindyebo Municipality, Eastern Cape - Pamela Mda; Don O’Mahony; Parimalarani Yogeswaran; Graham Wright (African Journal of Primary Health Care & Family Medicine, 2013)
Background: In South Africa the teenage fertility rate is high. About 42% of women have their sexual debut by 18 years of age and 5% by 15. These young women are also at risk of sexually transmitted infections (STIs) and human immunodeficiency virus (HIV) infection. Despite widespread availability of contraception, 18% of sexually active teenagers do not use any. Previous research on the knowledge of, attitudes to and practices of contraception by teenagers has focused on older adolescents.